Advokasi Greenpeace Terhadap Perusakan Lingkungan Hidup - Ramdhani P, Barik (Jurnal Al Tasyri'iyyah, 2023)
In order to realize the principles of sustainability and sustainability towards the environment, of course, it must depart from legal awareness by humans that everyone bears obligations and responsibilities towards future generations and towards each other in one generation by making efforts to preserve the carrying capacity of ecosystems and improve the quality of the environment. In a democracy that guarantees freedom of association and organization guaranteed by the Constitution to realize environmental concern, there is an international organization called Greenpeace, headquartered in Amsterdam, the Netherlands, has 2.8 million supporters worldwide and has regional offices in 41 countries, including Indonesia. . The organization has a sensitivity to environmental issues such as natural exploitation or environmental destruction by individuals or corporations. The legal umbrella covering environmental aspects in Indonesia has been poured into UU NO. 32 of 2009 concerning the protection and management of the environment as well as other laws and regulations, however, it is very unfortunate that environmental issues have become a serious matter involving moral, economic and social aspects. One of the cases of environmental destruction that often occurs in Indonesia is mining activities by corporations covering issues of corruption, health and the environment. The involvement and active role of the community is urgently needed to oversee cases of environmental destruction for future generations of children and grandchildren.